Influence of wastewater containing hexamethylenediamine on the livelihoods of hydrocoles of activated sludge - Іванова, Інна Миколаївна; Шатохіна, Юлія Вікторівна; Сапура, Олена Василівна; Тичина, Дмитро Олександрович (Eastern-European Journal of Enterprise Technologies, 2015)
The data regarding the ability of hydrocoles, immobilized on the carrier VIYA in bioreactors to exist in the real conditions of the aerobic process in biological pipelines in industrial wastewater treatment from hexamethylenediamine - chemical fiber production waste were obtained. The long-term keeping of these wastes in storage ponds threatens the environment since there are the signs of destruction of the coast covering, a risk of toxic substances getting into groundwater. Treatment of these wastes by means of the biological pipeline, the aerobic process in which is carried out using microorganisms, immobilized on the carrier VIYA from existing aerotanks is proposed. Process quality control was carried out using the quantitative accounting of the organisms of activated sludge on the conventional five-point scale. Two kinds of hydrocoles: small colorless filaments and unicellular alga Navicula from diatoms turned out to be the most resistant to hexamethylenediamine. Process quality control for changing the content of nitrite and nitrate ions with time during the first four weeks revealed their reduction respectively from 75.5mg/dm3 to 11.3mg/dm3 and from 867mg/dm3 to 219mg/dm3.